The Impact of Legal Abortion on Maternal Mortality - Sherajum Monira Farin; Lauren Hoehn-Velasco; Michael Pesko (Institute of Labor Economics (IZA), 2022)
Legal abortion has recently been suggested as an essential healthcare service. In this study, we consider whether abortion legalization over 1969-1973 improved women's health, measured by maternal mortality. Our event-study results indicate that legal abortion substantially lowered non-white maternal mortality by 30-40%, with 113 non-white maternal deaths averted nationally in the first year abortion became legal. We also find that early state-level legalizations were crucial, and more influential than the Roe v. Wade decision itself.
Keywords: I18; J13; K38; H75; 330; abortion; legal abortion; maternal mortality; Roe v. Wade; maternal health